2015
DOI: 10.1021/jacs.5b09526
|View full text |Cite
|
Sign up to set email alerts
|

Double FLP-Alkyne Exchange Reactions: A Facile Route to Te/B Heterocycles

Abstract: 1-Bora-4-tellurocyclohexa-2,5-diene undergoes sequential [4 + 2] cycloadditions/alkyne-elimination reactions to incorporate 2 equiv of terminal alkyne with the loss of diarylalkyne, affording access to a series of 11 new tellurium-boron heterocycles. These alkyne exchange reactions proceed regioselectively and can tolerate a variety of functional groups, thus providing the potential for further derivatization. The mechanism of the exchange reaction is confirmed by a DFT study to involve the interaction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…1,2,4 The reactivity of the alkynes depends on the C≡C bond nature and where the C≡C bond reactivity is usually influenced by its substituents. Currently, only a handful of (F)LP–alkyne cycloadditions to zwitterionic heterocycloalkenes of A, 7,8 B, 9 C, 10 D, 11 and E 5,6 types have been documented (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4 The reactivity of the alkynes depends on the C≡C bond nature and where the C≡C bond reactivity is usually influenced by its substituents. Currently, only a handful of (F)LP–alkyne cycloadditions to zwitterionic heterocycloalkenes of A, 7,8 B, 9 C, 10 D, 11 and E 5,6 types have been documented (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…A significant relevant example showed that 1-bora-4-tellurocyclohexa-2,5-diene undergoes subsequent [4+2] cycloaddition/alkyne-elimination via a Te/B FLP-type mechanism, reported by Stephan et al . 56 . These results prompted us to examine the thermal stability of the [4+2] cycloadducts 7 and 8 .…”
Section: Discussionmentioning
confidence: 99%
“…71 Thus, N-t-Bu-BN indole 41 is more nucleophilic in EAS than its carbonaceous counterpart and displays the classical indole-type regioselectivity (i.e., at the 3-position) (Scheme 8). 74 More recently, the same authors demonstrated further reactivity of these heterocycles, providing access to unsymmetrically substituted tellurium-boron based heterocycle. 75 Unusual reactivity has been noted for 1,3,2,5-diazadiborine 45 containing a formal B(+ 1)/B(+ III) mixed valence system in the aromatic six-membered B 2 C 2 N 2 ring.…”
Section: Scheme 3 Schemementioning
confidence: 97%